17.5: Invited Paper: Latest Development of Soluble OLED Materials and its Application to Mid‐ to Large‐sized Panel Production. (26th August 2021) - Fukushima, Daisuke; Tanaka, Shinya; Kakimoto, Hidenobu; Yamada, Takeshi
Abstract : We present the latest status of high performance OLED material development based on conjugated polymer technologies. The material which shows high performance is very suitable for printed OLED panel fabrication. New materials to reduce degradation from exciton realized better device lifetime. Key parameters have been identified to achieve high performance of ink jet printed (IJP) device. New materials for higher resolution panel fabrication have been developed and they provide wider application of IJP devices.